Development of a Gymnastics Movement through Exploration of the Cultural Values of the Aceh Rampoe Dance in Langsa City - Yoki Afriandy Rangkuti; Rizkei Kurniawan; Dedi Andriansyah; Muhammad Fauzan Isma (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
This study is a study that explores cultural values and develops a gymnastic movement that originates from the Aceh Rampoe dance in Langsa City. The research method used is a combination of qualitative research and development (Research & Development) from Brog and Gall. In the part of exploring the cultural values of the Rampoe Aceh dance, qualitative research methods are used with a holistic approach through in-depth interviews and direct observation at dance studios. Historical analysis of this dance is not a traditional Aceh dance that has existed for a long time. accordance with the terminology of the naming "Rampoe" which in Indonesian translation means "mixture", then this is the essence of the Aceh Rampoe dance. This dance is created and developed by combining or a mixture of several types of traditional Acehnese dances, such as the Likok dance, the Saman dance, and the Seudati dance. At each movement and the translation of the meanings contained in the Rampoe dance, it shows a variety of life messages related to the orientation of cultural values, namely first, the connection between the essence of a life of the Acehnese people (MH), and secondly related to the nature of the relationship between the Acehnese people and others. human (MM). A cultural value orientation that leads to the essence of life in oneself which is a creature that is created and has the creator, as well as relationships with other creatures (humans). So it requires a way to remind oneself to build a relationship between the creator and the creator (Allah SWT), which is accommodated by the element of religiosity that is felt in the lyrics of the Rampoe dance which are full of recitations of shahada and Shalawat. The Rampoe dance movement consists of Nyap (bending), moving steps, Rheng (horizontal movement), Asek which is a movement of turning the head from right to left, Ketrip Jaroe which is a movement in the form of snapping fingers, Nyet which is the body resting on the feet, then Dhet namely the movement of shrugging while the hand is slapped to the rhythm of the song, Gudam Kaki, and Puta Taloe, which is moving alternately between dancers.